Implementasi Bauran Pemasaran 7P dalam Meningkatkan Volume Penjualan UKM Ampuh di Kabupaten Kediri pada masa Pandemi Covid-19 - Istofia Zulfa; Tuwis Hariyani (Jurnal Multidisiplin Madani, 2022)
During the pandemic, many businesses, including SMEs, experienced a slump due to a decrease in sales volume. To maintain the survival of SMEs during the COVID-19 pandemic, an appropriate marketing strategy management is needed. Therefore, this study aims to describe the implementation of the 7P marketing mix in increasing sales volume, and to find out the factors that hinder and support its implementation. This type of research is descriptive qualitative. The variable being tested is the 7P marketing mix strategy (Kotler and Keller) in increasing sales volume. Data collection was carried out in March-June 2021 with interviews, observations, and documentation. The analysis technique uses interactive model data analysis, checking the validity of the data using triangulation. Research shows that AMPUH SMEs are successful in implementing the 7P marketing mix strategy in increasing sales, namely to attract consumers' interest by developing a sustainable competitive advantage.